THE ROLE OF VIRTUAL REALITY IN DENTAL EDUCATION AND TRAINING - Ibrahim Meslem Alazmi, Norah Mutiq Alshahrani, Salman Mohammed Alanazi, Mona Awad Almutairi, Waad saad aldossari, Nasr Tarrah Almajedi, Meshari Mutiq Alshahrani, Osama Saeed Alyami, Adel Abdullah Alanazi, ,; Shuaa Alhumidi Alanazi, Sarah Falah Alenezi, Ahmed Abdulrhman Alshebl, Njood Ahmed Gmari, Abdulrahman Saud Mohammed Alsuliman, Fawaz Marfoua Alshammari, (Chelonian Research Foundation, 2022)
Virtual reality and active digital models have been increasingly used in dentistry education to provide dental students with training prior to their engagement with actual patients. The employment of virtual tools in dentistry education has been supported by scientific data. Recent articles have shown that virtual and tactile technologies may provide favorable results in dental education. The objective of this systematic review was to assess the impact of virtual technologies on dental education outcomes and to investigate the perspectives of dental students and instructors on these technologies. A comprehensive search was performed in PubMed, Scopus, MEDLINE (via EBSCO), The Cochrane Library (via Wiley), Web of Science Core Collection (via Thomson Reuters), and Dentistry and Oral Science source (via EBSCO) using the keywords "student" and "dental" in conjunction with "education" and "dental," as well as "virtual reality," "augmented reality," "haptics," "simulation," "dentistry," and "dental medicine." The assessment of the submitted information's quality was conducted in accordance with the guidelines outlined in the Recommended Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement for systematic reviews. For this study, a grand total of 73 publications were taken into account. Out of the chosen research, fifty-two demonstrated a noteworthy improvement in educational results, and virtual technologies were universally regarded favorably by all participants. Based on the constraints of this review, it seems that virtual technology enhances educational achievements among dentistry students. Additional research with bigger sample sizes and longer duration clinical trials is necessary to validate the potential beneficial effects of different virtual technologies on dentistry education outcomes Keywords: augmented reality, simulation, dentistry education, haptics, students, virtual reality, education.